The emergence and development of extremist currents in Islamic history (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon our most honorable Prophet Muhammad Al-Mustafa Al-Amin, his good and pure family, and his chosen companions. To proceed: